Bioinspired hyaluronic acid based nanofibers immobilized with 3, 4-difluorobenzylidene curcumin for treating bacterial infections - Patel, Pratikshkumar R.; Singam, Amarnath; Iyer, Arun K.; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Curcumin (Cur) is a natural polyphenol with multifaceted pharmacological functions, exploited extensively for biomedical applications. Traditionally curcumin is being used as an antimicrobial agent. However, to improvise the pharmacological properties, it is being modified synthetically. One of such modified Cur is 3, 4- difluorobenzylidene curcumin (CDF) which is aimed for enhancing the anti-cancer properties. Though there are reports on the studies of anti-cancer properties involving CDF, the anti-bacterial property is yet to be demonstrated. Accordingly, in our studies, we prepared bioinspired hyaluronic acid blends immobilized with CDF and fabricated non-woven nanofiber mats. These nanofiber mats were characterized and demonstrated in vitro cell culture studies, which involved cell viability, hemolysis, anti-bacterial and cell scratch assay to understand their efficacy in treating bacteria. The molecular docking studies of CDF and Cur were performed on the dihydrofolate reductase (DHFR) enzyme receptor, which is an essential protein of S.auerus (Staphylococcus aureus). The results of MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay, and hemolysis of the respective nanofiber mats with Cur and CDF showed non-toxicity and were compatible with blood cells. Further, the cell proliferation and adherence recorded >60% fibroblast cells for the nanofiber mats. The anti-bacterial property of Cur and CDF was similar. The in vitro release studies for the respective Cur and CDF loaded nanofiber mats recorded a release of 25 and 37%, respectively. From these studies, we concluded that the CDF sustained its antibacterial property in addition to the improved anti-cancer property; hence CDF being synergetic, it will have a better scope in cancer therapy.
Keywords: anti-bacterial; curcumin; nanofibers; tissue engineering; wound Healing

Blend of neem oil based polyesteramide as magnetic nanofiber mat for efficient cancer therapy - Patel, Pratikshkumar R.; Singam, Amarnath; Dadwal, Arun; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Stearic acid-coated magnetic nanoparticles (SMN) and FU (5-Fluorouracil) were immobilized in the blends of neem oil-based polyesteramide and fabricated as nanofiber mat (NM) for controlled release of FU under the influence of an external magnetic field for targeted drug delivery to treat cancer efficiently. Analyzed the surface morphology of the fibers using E-SEM, it was observed that the fibers were smooth with the diameter ranging from 250 to 450 nm. TEM studies showed the uniform distribution of SMN in the nanofibers. The physico-chemical properties of NM and raw materials were analyzed using FTIR, TGA, and XRD. The results suggested that the polymers were well blended. In-vitro FU release studies of the NMs recorded a significant difference in the cumulative percentage of FU release from SMN-NMs. The SMN-NMs released 95% of FU in 4 h, whereas, NMs released 83% of FU in 24 h. The cell viability assay for the NM was evaluated in the L929 mouse fibroblast cells, where >75% of cells were viable. The hemolysis assay for the developed SMN-NF showed <5% of hemolysis, which indicated the NMs were safe for application. The anti-cancer activity of FU loaded SMN-NF was analyzed in the MCF-7 cancer cell line, which recorded more than 50% cell death within 24 h. From SQUID analysis, we found that the 10% SMN were superparamagnetic in nature, the magnetization at 30 kOe was observed to be 4.3 emu/g. Based on the in vitro results, we concluded that the developed SMN-NMs are recommended for in vivo studies to understand their efficacy for the targeted drug delivery to treat cancer.
Keywords: 5-Fluorouracil; drug release; electrospinning; Magnetic nanoparticles; nanofibers; Stearic acid